2020
DOI: 10.1007/s10826-020-01714-4
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Parenting Programs in Non-clinical Contexts: A Qualitative Review of Child Outcomes and Programs, and Recommendations for Future Research

Abstract: Mindful parenting programs, providing mindfulness training for parents and caregivers, have been gaining increasing attention in recent years. Parents participating in these programs have reported benefits in emotional awareness, listening, and parent-child relationships at post-intervention.Considering that many mindful parenting programs aim to train parents generally, rather than specifically targeting parents of clinic-referred or diagnosed children, it is necessary to ascertain the impact of these program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…For what concerns mindful parenting programs applied to typically developing samples, relatively limited studies with mixed results have been described [12,13]. Mindful parenting interventions have been proposed to parents at different times of their experience.…”
Section: Mindful Parenting Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For what concerns mindful parenting programs applied to typically developing samples, relatively limited studies with mixed results have been described [12,13]. Mindful parenting interventions have been proposed to parents at different times of their experience.…”
Section: Mindful Parenting Interventionsmentioning
confidence: 99%
“…Mindful parenting interventions have also been proposed to parents of children and adolescents, reducing parenting stress with a slight improvement in youth outcomes [15]. However, more research on non-clinical populations is needed to understand the effect of these programs as preventative benefits [12,13].…”
Section: Mindful Parenting Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, colleagues(2010, 2015) have compared the effects of SFP and MSFP, and the results have shown similar effects of SFP and MSFP in improving parenting skills and children outcomes. Thus, whether mindful parenting has a unique impact on parenting skills and children outcomes is still unclear (Chen et al, 2017;Kil & Antonacci, 2020).…”
Section: Cultivating Mindful Parentingmentioning
confidence: 99%
“…The results of 6 articles investigating the effects of mindful parenting programs on children, in which parents of children without any clinical diagnosis and showing normal development participate; It has been found that mindful parenting is effective but its effect on children's psychosocial functioning is limited (Kil & Antanocci, 2020).…”
Section: The Effects Of Being a Mindful Parent On The Parent-child Relationshipmentioning
confidence: 99%